Magnetic resonance imaging T1 and T2 mapping provide complementary information on the bone mineral density regarding cancellous bone strength in the femoral head of postmenopausal women with osteoarthritis. (May 2019) - Endo, Kaori; Takahata, Masahiko; Sugimori, Hiroyuki; Yamada, Satoshi; Tadano, Shigeru; Wang, Jeffrey; Todoh, Masahiro; Ito, Yoichi M.; Takahashi, Daisuke; Kudo, Kohsuke; Iwasaki, Norimasa
Abstract: Background: Since bone mass is not the only determinant of bone strength, there has been increasing interest in incorporating the bone quality into fracture risk assessments. We aimed to examine whether the magnetic resonance imaging (MRI) T1 or T2 mapping value could provide information that is complementary to bone mineral density for more accurate prediction of cancellous bone strength. Methods: Four postmenopausal women with hip osteoarthritis underwent 3.0-T MRI to acquire the T1 and T2 values of the cancellous bone of the femoral head before total hip arthroplasty. After the surgery, the excised femoral head was portioned into multiple cubic cancellous bone specimens with side of 5 mm, and the specimens were then subjected to microcomputed tomography followed by biomechanical testing. Findings: The T1 value positively correlated with the yield stress ( σ y ) and collapsed stress ( σ c ). The T2 value did not correlate with the yield stress, but it correlated with the collapsed stress and strength reduction ratio ( σ c / σ y ), which reflects the progressive re-fracture risk. Partial correlation coefficient analyses, after adjusting for the bone mineral density, showed a statistically significant correlation between T1 value and yield stress. The use of multiple coefficients of determination by least squares analysis emphasizes the superiority of combining the bone mineral density and the MRI mapping values in predicting the cancellous bone strength compared with the bone mineral density-based prediction alone. Interpretation: The MRI T1 and T2 values predict cancellous bone strength including the change in bone quality. Highlights: There are few non-invasive methods for assessing bone volume and quality. Magnetic resonance imaging T1 map value reflects underlying fracture risk. Magnetic resonance imaging T2 map value helps predict progressive re-fracture risk. Magnetic resonance imaging complements bone mineral density to predict bone strength.